Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1365-2788.1999.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity and the promotion of activity among adults with severe intellectual disability living in community residences: the impact of training staff in active support

Abstract: Active support, a package of procedures which includes activity planning, support planning and training on providing effective assistance, was introduced in five community residences serving 19 adults with severe intellectual disability following a multiple baseline design. The residents were directly observed to ascertain the level of assistance they received from staff and their engagement in activity. The introduction of active support increased the levels of assistance residents received, their engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
255
8
12

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(282 citation statements)
references
References 25 publications
6
255
8
12
Order By: Relevance
“…This curriculum was, however, developed for children with PIMD and its effects are limited to changes in the acquisition of motor skills (van der Putten et al, 2005). Another wellknown intervention for people with severe and profound intellectual disability is active support (Beadle-Brown, Hutchinson, & Whelton, 2012;Beadle-Brown et al, 2014;Jones et al, 1999), but its applicability and effectiveness in people with PIMD has not yet been studied (Maes, Lambrechts, Hostyn, & Petry, 2007). Further work on the role of professionals, fundamental knowledge about the course of motor development, and the development of movement-oriented interventions is required to reduce inactivity in the daily lives and care of people with PIMD.…”
Section: Discussionmentioning
confidence: 99%
“…This curriculum was, however, developed for children with PIMD and its effects are limited to changes in the acquisition of motor skills (van der Putten et al, 2005). Another wellknown intervention for people with severe and profound intellectual disability is active support (Beadle-Brown, Hutchinson, & Whelton, 2012;Beadle-Brown et al, 2014;Jones et al, 1999), but its applicability and effectiveness in people with PIMD has not yet been studied (Maes, Lambrechts, Hostyn, & Petry, 2007). Further work on the role of professionals, fundamental knowledge about the course of motor development, and the development of movement-oriented interventions is required to reduce inactivity in the daily lives and care of people with PIMD.…”
Section: Discussionmentioning
confidence: 99%
“…The consistent finding is that when well implemented, active support improves outcomes for people with intellectual disabilities across a number of domains: time spent engaged in meaningful activities and social interactions (Beadle-Brown, Hutchinson, & Whelton, 2012;Felce et al, 2000;Felce, de Kock, & Repp, 1986;Felce & Perry, 1995;Jones et al, 1999;Mansell, 1994;Mansell, Beadle-Brown, & Bigby, 2013;Mansell, Beadle-Brown, Macdonald, & Ashman, 2003;Mansell, Beadle-Brown, Whelton, Beckett, & Hutchinson, 2008;Thompson, Robinson, Dietrich, Farris, & Sinclair, 1996), participation in household and community-based activities (Jones, Felce, Lowe, Bowley, Pagler, Gallagher, et al, 2001;Stancliffe, Harman, Toogood, & McVilly, 2007), improved skills (Felce et al, 1986;Mansell, Ashman, Macdonald, & Beadle-Brown, 2002;Mansell, McGill, & Emerson, 2001), improved choice (Beadle-Brown, Hutchinson, et al, 2012), reduced challenging behaviour (Beadle-Brown, Hutchinson, et al, 2012;Jones et al, 2013;Koristsas, Iacono, Hamilton & Leighton, 2008;Stancliffe, McVilly, Radler, Mountford, & Tomaszewski, 2010), and mental health issues such as depression (Stancliffe et al, 2007). In a 2012 study, Beadle-Brown, Beecham, et al (2012) confirmed earlier research and demonstrated no differences in hours of staff or overall costs of care in services where active support was stronger compared to those where it was weaker.…”
mentioning
confidence: 84%
“…With regard to the quality of interactions, previous research (Felce et al 2000;Jones et al 1999;Shepherd, Muijen, Dean & Cooney 1995) suggests that when users are less able and the environment is particularly large (as in Dc2), then more negative interactions can be observed. Very few negative interactions were noted in this study in either day centre.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the quality of staff-client interaction, rather than just its quantity, may require that staff be trained in communicational skills in addition to 'active support' (Jones, Perry, Lowe, Felce, Toogood, Dunston, Allen & Pagler 1999;McConkey, Morris & Purcell, 1999).…”
Section: Discussionmentioning
confidence: 99%